Techno-Economic Impact of Using On-Grid and Off-Grid PV Solar Systems in West Bank (Masoud village as a case study) - Leena Mahmoud Rabee'a Ammous (My University, 2016)
There are some Palestinian villages and communities still have no access to electricity as they are far from the electric grid as well as there are economic and political obstacles .This thesis presents three energy supply alternatives for such villages and communities represented in centralized PV system, decentralized PV system and the option of expanding the electrical network. The detail design of these systems and the corresponding economical and financial assessment are illustrated in details as well. A software is designed to estimate the economic and financial indicators in order to compare between the proposed alternatives which is mainly based on the annuity cost of energy. A small community in Palestinian territories in Jenin governorate is taken as case study. The results show that the cost annuity for centralized PV system, decentralized PV system and expanding the electrical network are 1.335NIS/kWh, 1.344NIS/kWh and 7.289NIS/kWh respectively. The implementation of the proposed centralized PV system reduces the amount of CO2, SO2 and NO to about 4 tons, 30 tons and 18 tons, respectively. The cost of electrical energy produced by a grid connected PV power system is 0.509 NIS/kWh in case the electrical network is expanding for Masoud village. The impact of applying feed in tariff (FIT) policy is studied and analyzed.

هناك بعض القرى والتجمعات الفلسطينية التي لم يصلها الكهرباء حتى وقتنا الحاضر بسبب بعدها عن الشبكة الكهربائية وكذلك بسبب العقبات الاقتصادية والسياسية.تقدم هذه الأطروحة ثلاثة بدائل لإمدادات الطاقة لهذه القرى و التجمعات ممثلة في نظام الخلايا الشمسية المركزية واللامركزية وخيار توسيع الشبكة الكهربائية. وتم توضيح تصميم هذه النظم والتقييم الاقتصادي والمالي لكل نظام. وتم تصميم برنامج لتقدير المؤشرات الاقتصادية والمالية من أجل المقارنة بين البدائل المقترحة والتي تقوم أساسا على تكلفة الكيلووات الواحد للطاقة. وتم أخذ تجمع صغير في الأراضي الفلسطينية في محافظة جنين كحالة دراسية. وأظهرت النتائج أن تكلفة وحدة الطاقة لنظام الخلايا الشمسية المركزية، نظام الخلايا الشمسية اللامركزية وتوسيع الشبكة الكهربائية هي1,335شيكل / كيلو واط في الساعة، 1,344شيكل / كيلو واط في الساعة و7,289شيكل/ كيلو واط في الساعة على التوالي. وقد تبين أن تنفيذ نظام الخلايا الشمسية المركزية المقترح يقلل من كمية CO2، SO2 وCO إلى حوالي 4 طن و 30 طن و 18 طن على التوالي. تكلفة الطاقة الكهربائية التي تنتجها نظام الخلايا الشمسية المربوطة على الشبكة هي 0,509 شيكل / كيلو واط في الساعة في حالة تم توسعة الشبكة الكهربائية لقرية مسعود.وتم دراسة وتحليل أثر نظام التعرفة العائد.
الآثار التكنولوجية والإقتصادية لأنظمة الخلايا الشمسية المربوطة والغير مربوطة مع الشبكة الكهربائية في الضفة الغربية: قرية مسعود كحالة دراسية